2020
DOI: 10.1111/jdv.16694
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted infections during the COVID‐19 outbreak: comparison of patients referring to the service of sexually transmitted diseases during the sanitary emergency with those referring during the common practice

Abstract: performing serology for the viral infections associated with cutaneous manifestations, for example parvovirus B19 and enterovirus. Most of them reported itching and burning sensation. Only two of them referred pain. They were variably symptomatic for the respiratory tract, but none of them had such a severe lung involvement as to require intubation. One of them was completely asymptomatic, and only the acral vascular manifestation led us the suspicion of coronavirus infection. In six of the patients showing ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 3 publications
2
14
0
1
Order By: Relevance
“…Our nationwide results are in line with previous studies from Italy. 7 8 In Spain, lockdown measures appeared to reduce STI incidence; however, restrictions in Finland were not as strict. 9 An increase in CT diagnoses was seen in July (after nightlife reopened), but this could be due to seasonal variation.…”
mentioning
confidence: 99%
“…Our nationwide results are in line with previous studies from Italy. 7 8 In Spain, lockdown measures appeared to reduce STI incidence; however, restrictions in Finland were not as strict. 9 An increase in CT diagnoses was seen in July (after nightlife reopened), but this could be due to seasonal variation.…”
mentioning
confidence: 99%
“…The significant decrease of venereal diseases search terms during the COVID-19 pandemic may be related to the fact that decreased extramarital sex activity due to social distancing, gathering, and a campaign that directs everyone to "stay-at-home. 15 Although during 2 months of the COVID-19 pandemic there was a decreasing number of "botox" search terms in both countries, then it increased approximately to the same level of the previous year on June 1, 2020. Despite the stay at home policies, people are still active on social media and continue to share their daily social life during the pandemic.…”
Section: Discussionmentioning
confidence: 98%
“…After the COVID-19 pandemic, number of patients who request dermatology outpatient clinic visits was decreased in many countries because of stay at home policies in order to deal with the current global pandemic. 2,14,15 Thus, certain diseases that may be increased in number after the COVID-19 pandemic remained concealed. Dermatology outpatient clinics represent only the tip of the iceberg during the COVID-19 pandemic days.…”
Section: Discussionmentioning
confidence: 99%
“…In venereology, the pandemic has brought remarkable developments; while many people assumed that STD would go down during the lockdown, this obviously was not the case as a study from Northern Italy showed: only the number of prophylactic visits went down but not the incidence of venereological diseases, in which syphilis even showed an increase 8 …”
Section: Covid‐19 and Dermatologymentioning
confidence: 99%